Room Temperature, Open-Flask C–P Bond-Formation on Water under Catalyst-Free Conditions - Choudhary, Rakhee; Bai, Rekha; Singh, Pratibha; Sharma, Mahesh C.; Badsara, Satpal Singh (SynOpen, 2018)
A catalyst-free C–P bond-formation in an open flask at room temperature between isatin derivatives and phosphorus surrogates on water is described. Isatin derivatives possessing different substitutes underwent C–P coupling reaction with a variety of phosphine oxides under the reaction conditions employed, providing the desired products in up to quantitative yields.
Keywords: catalyst-free; C–P bond formation; isatin